ANALISIS KOMPARASI INDEKS ISLAMIC SOCIAL REPORTING PERUSAHAAN PERBANKAN SYARIAH DAN PERUSAHAAN GO PUBLIK YANG LISTING DI JAKARTA ISLAMIC INDEX - Citra Indah Merina; Verawaty Verawaty (Universitas Muhammadiyah Metro, 2016)
Islamic Social Index Reporting (ISR) is an index that measures the level of social disclosure that according to Islamic principles presented in the company's annual report. This research is aimed to compare the quality of corporate social reporting between the two groups of samples, namely the Islamic banking companies and companies listed in the Jakarta Islamic Index (JII) by using ISR index. This study uses a statistical test Mann Whitney test to compare based on six criteria; Funding and Investment, Products and Services, Employees, Community, Environment, and Corporate Governance between those two groups. The result of this study indicates that the Islamic banking company revealed more based on ISR index than the companies listing in the JII with exception for products and services where the value of first and second group is only slightly in 15.76%. The research proves empirically that the disclosures made by the company that actually operates with the sharia concept as Islamic banking companies are indeed better meet the ISR index than conventional companies listing in the JII. Keywords: Finance and Investment, Products/Services, Employee, Society, Environment, Corporate Governance, Mann Whitney Test